Mixed convection and entropy generation of nanofluid flow in a vented cavity under the influence of inclined magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Springer Heidelberg, 2019)
In this study, mixed convection and entropy generation in a vented cavity with inlet and outlet ports are examined under the effects of an inclined magnetic field. Galerkin weighted finite element method was used for the solution of the governing equations. The numerical simulations are performed for various values of Reynolds numbers (between 100 and 500), Hartmann number (between 0 and 50) and solid particle volume fractions of CuO nanoparticles (between 0 and 4%). Different walls and domains of the computational model are considered for the heat transfer and entropy generation analysis. It was observed that at low Reynolds number number, magnetic field has the potential to enhance the heat transfer at the highest strength while the effect of magnetic field is to reduce the convection at higher Reynolds number. The contributions of different hot walls to the overall heat transfer change considerably with the change of Hartmann number while the effect of magnetic inclination angle is marginal. Inclusion of nanoparticle results in heat transfer enhancement in the absence and presence of magnetic field and the amount of enhancement is 25-27% at the highest value of solid nanoparticle volume fraction. Different parts of the cavity contribute differently to the overall entropy generation when Hartmann number varies while the overall entropy generation first decreases and then increases when the value of Hartmann number increases. The addition of nanoparticles increases the overall entropy generation rate.
Keywords: Mhd Natural-Convection; Backward-Facing Step; Heat-Transfer; Forced-Convection; Square Cavity; Porous Cavity; Triangular Cavity; Ventilated Cavity; Pulsating Flow; Cylinder